1992
DOI: 10.1042/bj2850391
|View full text |Cite
|
Sign up to set email alerts
|

A member of the eukaryotic subtilisin family (PC3) has the enzymic properties of the type 1 proinsulin-converting endopeptidase

Abstract: PC3, a mammalian homologue of the yeast subtilisin-like proteinase Kex2, was expressed in Xenopus oocytes and its activity was characterized. PC3 cleaved human proinsulin at one of the two dibasic sites (KTRR32 but not LQKR65). The specificity, inhibitor profile, pH optimum (5.5) and Ca2"-dependence (Ko5 = 2.5-3 mM) paralleled those of the insulingranule type 1 endopeptidase activity, suggesting a role for PC3 in the conversion of prohormones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
0

Year Published

1992
1992
2003
2003

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(72 citation statements)
references
References 29 publications
4
67
0
Order By: Relevance
“…The data for PC2 activity in COS cells are in agreement with the specificity of type II activity studied in vitro [181]. Intriguingly, whereas PCl appears able to cleave proinsulin at both junctions in COS cells, it can only cleave at the B-chain/C-peptide junction in vitro [230], and a similar selective substrate specificity has been shown for the type I enzyme in vitro [181]. It is, however, difficult to compare the in vivo and in vitro studies.…”
Section: Furinsupporting
confidence: 74%
See 2 more Smart Citations
“…The data for PC2 activity in COS cells are in agreement with the specificity of type II activity studied in vitro [181]. Intriguingly, whereas PCl appears able to cleave proinsulin at both junctions in COS cells, it can only cleave at the B-chain/C-peptide junction in vitro [230], and a similar selective substrate specificity has been shown for the type I enzyme in vitro [181]. It is, however, difficult to compare the in vivo and in vitro studies.…”
Section: Furinsupporting
confidence: 74%
“…There is a precise alignment of Asp, His and Ser in the catalytic domains of the different members, although a highly conserved Asn residue has been replaced by Asp in PC2, an interesting mutation since this residue has been shown to play an important role in catalysis in the bacterial subtilisins [227,228]. PCl and PC2 have an optimal enzyme activity at acidic pH [229][230][231][232], while furin has a broad, neutral pH optimum [233]. This family of enzymes has also in common the fact that Ca2l is an essential requirement, although the concentration dependency varies greatly [181].…”
Section: The Search For the Conversion Endoproteases Purification Of mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, its clearcut localization to the islets of Langerhans supports a role for this protease in proinsulin processing. Recent studies of Bailyes et al (48) analysis (data not shown) and which require a more acidic environment for optimal activity (36,48 …”
Section: Discussionmentioning
confidence: 99%
“…The fact that IAPP is co-localized with insulin in fl-cell granules, and human proinsulin is processed by the combined action of PC2 and PC3 [13] suggests that these enzymes might be involved in proIAPP processing. Alternatively, proIAPP may be processed in a separate compartment, possibly by furin.…”
Section: Introductionmentioning
confidence: 99%